Experience of treating extensive drug resistant tuberculosis patients including continuous use of bedaquiline, in Tomsk Region: immediate and postponed results - P. N. Golubchikov; E. A. Kruk; S. P. Mishustin; T. I. Petrenko; D. A. Kudlay (Туберкулез и болезни лёгких, 2019)
The objective of the study: to evaluate the efficacy and safety of treatment of tuberculosis patients with pre-extensive drug resistance and extensive drug resistance (XDR-TB) with regimen V using new anti-tuberculosis drugs including continuous treatment with bedaquiline.Subjects and methods. The treatment efficacy and safety were assessed in 39 patients treated with regimen V. Of them, 17 (43.6%) suffered from fibrous cavernous tuberculosis, 31 (79.5%), and 9 (23.1%) were HIV positive.Results. Treatment efficacy: 32 (82.0%) were cured, 1 (2.6%) was treatment failure, 4 (10.2%) did of non-tuberculosis, 2 (5.1%) defaulted from treatment. 23 (69.7%) patients took bedaquiline for the entire course of chemotherapy (the average duration made 19.3 months). Of them, 22 (95.6%) were cured, 1 (4.4%) had treatment failed. It was observed that the drug was well tolerated.Adverse events resulted in the cancellation of drugs were documented in 9 (23.1%) patients. After sputum conversion, 30 (76.9%) patients were treated using hospital-substituting technologies, including 10 of them who were treated under direct observation by video. Post-treatment follow-up is carried out in 28 out of 32 (2 changed their place of residence, 2 died of non-tuberculosis) of the treated patients, the average duration of follow-up have made 11.7 ± 6.3 months, the patients are relapse free.